2017
DOI: 10.1007/s13226-017-0248-1
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations, large deviations and rigidity in hyperuniform systems: A brief survey

Abstract: We present a brief survey of fluctuations and large deviations of particle systems with subextensive growth of the variance. These are called hyperuniform (or superhomogeneous) systems. We then discuss the relation between hyperuniformity and rigidity. In particular we give sufficient conditions for rigidity of such systems in d = 1, 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 39 publications
2
66
0
2
Order By: Relevance
“…Secondly, our findings are at variance with the behaviour observed in invariant models, as for instance the β-Gaussian, β-Wishart or β-Cauchy ensembles, in which there is no intermediate regime and, instead, the typical (Gaussian) and the large deviation regimes match smoothly [10,31]. We hope that our exact results for the FCS in the complex Ginibre ensemble will be interesting for the rather wide community working on the FCS in matrix models and related Coulomb gas systems, and more generally on random or disordered hyperuniform systems [21,22]. Besides, the results found in the present work could be experimentally relevant, as it has recently been shown that the positions of the eigenvalues of the complex Ginibre ensemble (2) are in one-to-one correspondence with the positions of fermions in a 2d-rotating harmonic trap [41], a system which, in principle, can be realized experimentally (see e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, our findings are at variance with the behaviour observed in invariant models, as for instance the β-Gaussian, β-Wishart or β-Cauchy ensembles, in which there is no intermediate regime and, instead, the typical (Gaussian) and the large deviation regimes match smoothly [10,31]. We hope that our exact results for the FCS in the complex Ginibre ensemble will be interesting for the rather wide community working on the FCS in matrix models and related Coulomb gas systems, and more generally on random or disordered hyperuniform systems [21,22]. Besides, the results found in the present work could be experimentally relevant, as it has recently been shown that the positions of the eigenvalues of the complex Ginibre ensemble (2) are in one-to-one correspondence with the positions of fermions in a 2d-rotating harmonic trap [41], a system which, in principle, can be realized experimentally (see e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the variance grows like ∝ r, i.e. much slower than the area of the disk (∝ r 2 ) demonstrates the hyperuniformity of the fluctuations in this system [21,22]. Besides, a more detailed analysis of the CGF allows to show that all the cumulants, other than the first one, grow at most like √ N [41].…”
Section: A Regime Of Typical Fluctuationsmentioning
confidence: 90%
“…Pair correlation functions g2(x) of the URL model in 1D, cf. Eqs (7). and (C6), where the random displacement of each point in the lattice Z is uniformly distributed in [−a/2, a/2).…”
mentioning
confidence: 99%
“…All perfect crystals and quasicrystals are hyperuniform, but typical disordered many-particle systems, including gases, liquids, and glasses, are not. Disordered hyperuniform many-particle systems are exotic states of amorphous matter that have attracted considerable recent attention in physics and materials science because of their novel structural and physical properties [10][11][12][13][14][15][16][17][18][19][20]. According to the celebrated Riemann hypothesis, the nontrivial zeros of the zeta function lie along the critical line s = 1/2 + it with t ∈ R in the complex plane and thus form a one-dimensional point process.…”
Section: Introductionmentioning
confidence: 99%